2015
DOI: 10.1111/1440-1630.12241
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to social and community participation following spinal cord injury

Abstract: This study contributes to the evidence base regarding outcomes following SCI. Enabling engagement in meaningful activities in the community must be at the forefront of occupational therapy intervention, both at an individual client level and through advocacy and policy involvement, to improve the quality of life of people with SCI living in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
140
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(157 citation statements)
references
References 22 publications
10
140
2
5
Order By: Relevance
“…4,5 Rehabilitation efforts to promote engagement in meaningful community activities can also contribute to health-related quality of life. 58 Case formulations require accurate identification of those individuals at risk of experiencing poor psychosocial outcomes. 57 Validated self-reported health indices for the SCI group include condition-specific measures, such as the Spinal Cord Lesion Coping Strategies Questionnaire 50 and Moorong Self-Efficacy Scale, 59 which assess passive and active behavioural coping.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Rehabilitation efforts to promote engagement in meaningful community activities can also contribute to health-related quality of life. 58 Case formulations require accurate identification of those individuals at risk of experiencing poor psychosocial outcomes. 57 Validated self-reported health indices for the SCI group include condition-specific measures, such as the Spinal Cord Lesion Coping Strategies Questionnaire 50 and Moorong Self-Efficacy Scale, 59 which assess passive and active behavioural coping.…”
Section: Discussionmentioning
confidence: 99%
“…The urban integration is supposed to attend from 2016 with mass transportation about 63% of the population (4,080,277 habitants), a big improvement, compared to 2009 when it was attending only 18% (1,165,793 habitants) [27]. On the other hand, social aspects as seeking for a healthier life quality or respect the rights of disabled people, for example the access to parking spaces [28], only had a small impact in games time. A very important aspect during the bidding process to host the Games is usually the security, however it has no significantly long-term social impact [29].…”
Section: Politic and Social Aspectsmentioning
confidence: 99%
“…An individual's capacity to reintegrate into home and community life following SCI is a crucial aspect of establishing improvements in wellbeing and life satisfaction (Barclay et al, 2015;Boschen, Tonack & Gargaro, 2003;Larsson Lund, 2005). Research to date has demonstrated that social and community participation for people with SCI continues to be an area of ongoing challenge (Barclay, McDonald, Lentin & Bourke-Taylor, 2016;Carpenter et al, 2007;Lysack, Komanecky, Kabel, Cross & Neufeld, 2007;Noreau & Fougeyrollas, 2000). In a study of 136 people with SCI who were on average 11.5 years post-injury, Lysack and colleagues found a statistically significant relationship between perceived environmental barriers and community integration for adults with SCI (Lysack et al, 2007).…”
Section: Community Integration and Scimentioning
confidence: 99%